Teacher's Interest In Using Media Technology In Madrasah Diniyah Miftahussa'adah Mojoagung Jombang - Ali Muhsin (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Abstract: The function of technology develops rapidly as well as its use in the general field or in the Madrasah, especially in Madrasah Diniyah Miftahussa'adah. In its development, it invites several interests in some learning institutions in Madrasah Diniyah Miftahussa'adah to use the Book of Salaf. Previously the teaching of Madrasah Diniyah used the method of Salaf which is the book used is called a book of Salaf. However, the use of this book does not close the possibility of the Asatiz not to use the emerging methods of technology. Moreover, the existence of the Salaf books get bored in students’ perspective. However, in terms of learning method it can raise the interest of teachers in using media technology for learning at Madrasah Diniyah Miftahussa'adah. Keywords: method, technology.